ELEMENTS OF CONTROL THEORY APPLIED TO AN INVESTMENT PORTFOLIO IN THE CAPITAL MARKET. THE OPTIMAL TIME HORIZON FOR SELLING A PORTFOLIO - Tymiński, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The article presents a concept of capital management for assembling investment portfolios. Two optimization variants of a portfolio to be purchased are discussed. Portfolio I is structural, using the „traditional model”. To assemble Portfolio II, elements of reliability theory and the dynamic programming method were used. The article also analyses the sale of a portfolio with respect to the demand for financial instruments in the capital market. The presented concept dealing with rational investment decisions during transactions at the Warsaw Stock Exchange can also be used by managers to create an effective portfolio of financial instruments.